2021
DOI: 10.1002/pssr.202100278
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Insulator Transition via Ion Irradiation in Epitaxial La0.7Sr0.3MnO3−δ Thin Films

Abstract: Complex oxides provide rich physics related to ionic defects. For the proper tuning of functionalities in oxide heterostructures, it is highly desired to develop fast, effective, and low‐temperature routes for the dynamic modification of defect concentration and distribution. Herein, the use of helium implantation to efficiently control the vacancy profiles in epitaxial La0.7Sr0.3MnO3−δ thin films is reported. The viability of this approach is supported by lattice expansion in the out‐of‐plane lattice directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Similarly, metallicto-insulator and ferromagnetic-to-antiferromagnetic transitions can be achieved in La 0.7 Sr 0.3 MnO 3 thin films via controlling the vacancy defect concentration profile through He ion irradiation. 4 Various studies have been reported the fundamental discoveries on the effect on cationic radii and the local environment around the cations that lead to an order-disorder phase transformation. It has been seen that the tendency of phase transformation in pyrochlore structure oxides (A 2 B 2 O 7 ) from amorphous to disordered defect-fluorite phase grows with increasing size of the B-site cation (Ti to Zr).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, metallicto-insulator and ferromagnetic-to-antiferromagnetic transitions can be achieved in La 0.7 Sr 0.3 MnO 3 thin films via controlling the vacancy defect concentration profile through He ion irradiation. 4 Various studies have been reported the fundamental discoveries on the effect on cationic radii and the local environment around the cations that lead to an order-disorder phase transformation. It has been seen that the tendency of phase transformation in pyrochlore structure oxides (A 2 B 2 O 7 ) from amorphous to disordered defect-fluorite phase grows with increasing size of the B-site cation (Ti to Zr).…”
Section: Introductionmentioning
confidence: 99%
“…[ 31 ] A method to induce oxygen vacancy while maintaining the crystallinity of a film is ion irradiation; recently, the MIT of La 0.7 Sr 0.3 MnO 3 has been demonstrated by He ion irradiation. [ 32 ] The oxygen vacancies also degrade the ferromagnetism of La 0.7 Sr 0.3 MnO 3 , [ 33 ] which is preferable when intentionally creating a magnetically inactive region in an FM layer. Considering the unique features of oxide materials, one can expect flexible oxide‐based circuit design by inducing phase transitions in intended areas via lithography patterning, through which the conductivity at desired locations can be arbitrarily controlled from metal to insulator.…”
Section: Introductionmentioning
confidence: 99%